2017
DOI: 10.1039/c6ra26250c
|View full text |Cite
|
Sign up to set email alerts
|

Cellular-membrane inspired surface modification of well aligned ZnO nanorods for chemosensing of epinephrine

Abstract: Modified ZnO nanorods array to form a chemical sensor for neurotransmitters. The interspaces between the nanorods offer highly efficient immobilization of the lipid membrane containing the calixarene, which act as receptor molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Zinc oxide nanorod field-effect transistors (FETs) were monitored physiological conditions via the detection of glucose, cholesterol, and urea in the samples of mice’s blood, and diabetic dogs’ serum and blood [57]. Mohsin et al [189] reported using aligned ZnO nanorods for epinephrine sensing. Zinc oxide electrodes on flexible porous polyimide substrates were also developed for the detection of cardiac troponin [190].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Zinc oxide nanorod field-effect transistors (FETs) were monitored physiological conditions via the detection of glucose, cholesterol, and urea in the samples of mice’s blood, and diabetic dogs’ serum and blood [57]. Mohsin et al [189] reported using aligned ZnO nanorods for epinephrine sensing. Zinc oxide electrodes on flexible porous polyimide substrates were also developed for the detection of cardiac troponin [190].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In the case of EP and NE, there are almost no existing detection systems, which is opposite to DA [ 72 , 73 ]. It is much more difficult to detect EP or NE because of their rapid metabolism and in fact, these molecules do not possess any fluorescence properties [ 74 ].…”
Section: Fluorescent Biosensors For Determination Of Neurotransmitmentioning
confidence: 99%
“…In the case of epinephrine, there are just few existing detection systems, as opposed to dopamine or norepinephrine [12][13][14][15]. It is much more difficult to detect EP because of its rapid metabolism and due to the short epinephrine half-life in organisms [16]. Recently, an increase of interest in using the electrochemical biosensors and sensors in EP determination is observed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%